Exploration of nutritional and bioactive peptide properties in goat meat from various primal cuts during in vitro gastrointestinal digestion and absorption - Luasiri, Pichitpon; Sangsawad, Papungkorn; Pongsetkul, Jaksuma; Paengkoum, Pramote; Nakharuthai, Chatsirin; Suwanangul, Saranya; Katemala, Sasikan; Sujinda, Narathip; Pinyo, Jukkrapong; Chainam, Jarunan; Khongla, Chompoonuch; Sorapukdee, Supaluk (My University, 2024)
Objective: This research aims to explore the nutritional and bioactive peptide properties of goat meat taken from various primal cuts, including the breast, shoulder, rib, loin, and leg, to produce these bioactive peptides during in vitro gastrointestinal (GI) digestion and absorption. Methods: The goat meat from various primal cuts was obtained from Boer goats with an average carcass weight of 30±2 kg. The meat was collected within 3 h after slaughter and was stored at –80°C until analysis. A comprehensive assessment encompassed various aspects, including the chemical composition, cooking properties, in vitro GI digestion, bioactive characteristics, and the bioavailability of the resulting peptides. Results: The findings indicate that the loin muscles contain the highest protein and essential amino acid composition. When the meats were cooked at 70°C for 30 min, they exhibited distinct protein compositions and quantities in the sodium dodecyl sulfate-polyacrylamide gel electrophoresis profile, suggesting they served as different protein substrates during GI digestion. Subsequent in vitro simulated GI digestion revealed that the cooked shoulder and loin underwent the most significant hydrolysis during the intestinal phase, resulting in the strongest angiotensin-converting enzyme (ACE) and dipeptidyl peptidase-IV (DPP-IV) inhibition. Following in vitro GI peptide absorption using a Caco-2 cell monolayer, the GI peptide derived from the cooked loin demonstrated greater bioavailability and a higher degree of ACE and DPP-IV inhibition than the shoulder peptide. Conclusion: This study highlights the potential of goat meat, particularly cooked loin, as a functional meat source for protein, essential amino acids, and bioactive peptides during GI digestion and absorption. These peptides promise to play a role in preventing and treating metabolic diseases due to their dual inhibitory effects on ACE and DPP-IV.
Keywords: Bioactive Peptide; Bioavailability; Gastrointestinal Digestion; Goat Meat; Protein